Estimating the site quality of Cinchona pubescens (Rubiaceae) in La Palma montane forest, province of Chota, Peru. - Rufasto-Peralta, Yennifer L. (2023)
The genus Cinchona L. (Rubiaceae) has 23 species, of which 19 are distributed in Peru. Although it is a very important genus worldwide, its habitats are being degraded at an accelerated rate. No research on the site quality of these species has been conducted, making it difficult to devise habitat recovery plans. The objective of the research was to estimate the site quality of Cinchona pubescens Vahl., in La Palma montane forest, located in the district and province of Chota, Cajamarca region, Peru. Three circular plots of 500 m2 (r =12.6 m) were established, and the total height and circumference at breast height of the trees were measured. An analysis of variance was performed to evaluate the existence of site classes. Climatic, physiographic and edaphic variables were obtained and correlated with tree height to explain their relationship; in addition, a Principal Component Analysis was performed to explain the variability of the studied variables. No statistical difference was detected between the mean heights of the trees, since all the plots presented similar site quality. The edaphoclimatic factors were not correlated with height. However, the Principal Component Analysis showed that edaphic variables had a greater influence on the height of Cinchona pubescens Vahl. than climatic and topographic variables. This species grows in sandy loam soils, with a strongly acid pH and medium to high concentrations of some elements, such as organic matter, P, K and N.